(untitled) (Research, Society and Development, 2022)
Objectives: This research aims to analyze the impact of the pandemic by COVID-19 on access to intimate health of women in the Northeast region of Brazil. Methods: This is an observational, cross-sectional, and descriptive study, through its online questionnaire, with northeastern women from 18 years of age. The sample calculation was performed using the population parameter estimate equation, finding a minimum "n" of 385 people. The form was published through social networks, with the participation of 463 women. Results: The profile socio-demographic study was composed chiefly of white women (52.3%), between 18-24 years old (47.5%), and had health insurance (78.4%). Of the 100 women who did not have access to supplementary health, 56% depended exclusively on the SUS. Of the 463 participants, 63.8% consulted during the pandemic, 33% did not see, and 3.2% made appointments but had not yet gone. Among those that depended exclusively on the SUS, 67.3% were not attended, a percentage approximately twice as high as that of the general sample. As for the women who attended the visits, 44.5% faced some difficulty in accessing the consultation, and 84.3% of these limitations arose or worsened because of the pandemic. Conclusion: Although most participants had good conditions, one-third did not consult during the pandemic. Due to several factors, it is notorious that this period negatively impacted women’s health, reducing the number of queries and increasing access difficulties.